Preferential utilization of inorganic polyphosphate over other bioavailable phosphorus sources by the model diatoms Thalassiosira spp. (7th May 2019) - Diaz, Julia M.; Steffen, Rachel; Sanders, James G.; Tang, Yuanzhi; Duhamel, Solange
Summary: Polyphosphates and phosphomonoesters are dominant components of marine dissolved organic phosphorus (DOP). Collectively, DOP represents an important nutritional phosphorus (P) source for phytoplankton growth in the ocean, but the contribution of specific DOP sources to microbial community P demand is not fully understood. In a prior study, it was reported that inorganic polyphosphate was not bioavailable to the model diatoms Thalassiosira weissflogii and Thalassiosira pseudonana . However, in this study, we show that the previous finding was a misinterpretation based on a technical artefact of media preparation and that inorganic polyphosphate is actually widely bioavailable to Thalassiosira spp. In fact, orthophosphate, inorganic tripolyphosphate (3polyP), adenosine triphosphate (ATP) and adenosine monophosphate supported equivalent growth rates and final growth yields within each of four strains of Thalassiosira spp. However, enzyme activity assays revealed in all cultures that cell‐associated hydrolysis rates of 3polyP were typically more than ~10‐fold higher than degradation of ATP and the model phosphomonoester compound 4‐methylumbelliferyl phosphate. These results build on prior work, which showed the preferential utilization of polyphosphates in the cell‐free exudates of Thalassiosira spp., and suggest that inorganic polyphosphates may be a key bioavailable source of P for marine phytoplankton.